Предмет: Алгебра,
автор: Lacoster
Лёгкие примерчики, помогите люди добрые ;)
Приложения:
Ответы
Автор ответа:
0
вроде, так)))
...........................................
...........................................
Приложения:
Автор ответа:
0
Благодарю :)
Автор ответа:
0
1)(((a+3)*(a+3)+(a-3)*(a-3))/(a^2-9))/((2a^2+18)/(a^2-9))=((a^2+3a+3a+9)+(a^2-3a-3a+9))/(a^2-9))/((2a^2+18)/(a^2-9))=((2a^2+18)*(a^2-9))/((a^2-9)*(2a^2-18))=-1
2)(((m-4)*(m-4)-(m+4)*(m+4))/(m^2-16))/(32m/(m^2-16))=((m^2-4m-4m+16-m^2-4m-4m-16)/(m^2-16))/(32m/(m^2-16))=(-16m*(m^2-16))/(m^2-16)*32m)=-0,5
2)(((m-4)*(m-4)-(m+4)*(m+4))/(m^2-16))/(32m/(m^2-16))=((m^2-4m-4m+16-m^2-4m-4m-16)/(m^2-16))/(32m/(m^2-16))=(-16m*(m^2-16))/(m^2-16)*32m)=-0,5
Приложения:
Похожие вопросы
Предмет: Химия,
автор: yanaglonuik0805
Предмет: Русский язык,
автор: anaspankratowa
Предмет: Физика,
автор: sefico25
Предмет: Алгебра,
автор: Кошечка68
Предмет: Биология,
автор: Олькааааааа